Hand hygiene practices during meal preparation-a ranking among ten European countries - Octavian Augustin Mihalache; Paula Teixeira; Solveig Langsrud; Anca Ioana Nicolau (BMC, 2023)
Abstract Background The aim of this paper was to map consumers' food hygiene practices from 10 European countries and evaluate which demographic groups are more likely to be exposed to foodborne pathogens and establish a ranking of adherence to food hygiene practices in 10 European countries. Methods The research design consisted of a cross-national quantitative consumer survey regarding food safety and hygiene practices during meal preparation (SafeConsume project) and was conducted in ten European countries (France, Denmark, Germany, Greece, Hungary, Norway, Portugal, Romania, Spain and UK). The survey questions were based on recommended hand hygiene practices and on observed practices from a field study performed in 90 European households from six of the countries covered by the survey (France, Hungary, Norway, Portugal, Romania, and UK). SPSS Statistics 26 (IBM Software Group, Chicago, IL) was used for the descriptive and regression analyses of the data. Regression analyses were used to check the relation between demographic characteristics, country of origin and self-reported hand hygiene practices. Results According to the regression models, families with elderly members aged over 65 showed a higher tendency to follow proper hand washing practices compared to families without elderly members. Meanwhile, families with children under the age of 6 reported being up to twice as likely to wash their hands at critical moments compared to families without children. Overall, taking into consideration the likelihood of washing hands after touching raw chicken and the percentages scores for proper hand cleaning methods and key moments for hand washing, the rank of the countries regarding proper hand hygiene practices was the following: Denmark, Greece, Norway, Romania, Hungary, Germany, UK, Portugal, France, and Spain. Conclusions Information and education should point both at the key moments as suggested by the Royal Society for Public Health (RSPH) and the International Scientific Forum on Home Hygiene (IFH) and safe practices. Public health burden generated by improper hand washing may be significantly reduced if education is targeted on consumers' behaviour and practices.